Non-enzymatic modifications in metallothioneins connected to lipid membrane damages: structural and biomimetic studies under reductive radical stress. (Journal of proteomics, 2013)
UNLABELLED: Metallothioneins (MTs) are small cysteine-rich proteins with the ability to coordinate heavy metal atoms through metal-thiolate bonds, which are widely distributed among the animal and plant kingdoms. Multifunctional roles for MTs have been proposed, including their ability to scavenger various radicals and reactive oxygen species. In the present article we summarize available information of four MT polypeptides from different organisms, forming metal complexes with Zn(II), Cd(II) or Cu (I) ions. Non-enzymatic modifications of MTs under ionizing radiations and their consequences on the lipidic membrane compartment were studied by Raman spectroscopy and a biomimetic model, respectively. The latter is based on liposome technology and allows to measure the trans unsaturated fatty acid content as a result of reductive radical stress on MTs. BIOLOGICAL SIGNIFICANCE: The effect of radical stress on the cell metabolism and functions is a very active field of research connecting various disciplines in life sciences. In this contest tandem radical damage has been the subject of recent investigations that pointed out its harmfulness in the general scenario of establishing the consequences of radical stress. By using biomimetic models of tandem damage we have for the first time tested the capability of metallothioneins (MTs), small metalloproteins rich of Cys residues, to damage another cell compartment like lipid membranes when they are undergone to reductive radical stress. The connection of MT reactivity with membrane lipid transformation can give a contribution to the puzzling context of radical stress occurring to biomolecules and the role as biological signaling. To this purpose, MT polypeptides from different organisms, exhibiting different sequence peculiarities, have been analyzed here. The spectroscopic analysis of these systems has allowed to identify modifications affecting metal-thiolate clusters, cystines, and Met residues, acting as efficient interceptors of reducing radical species. The chemical mechanism involving sulfur-containing moieties under reductive conditions discloses new scenarios that bring to the loss of sulfur-centered radicals by desulfurization reactions that change the natural sequences of MTs. Ala is a genetically coded amino acid, therefore the mutation of Cys to Ala occurring to a sequence by the radical process so far discussed, corresponds to a post-translational modification. Research on such mutation connected also to a free radical stress will be important to contribute for a complete picture of the degeneration associated to diseases and aging. Analogously, the Met to Aba mutation occurring after reductive stress transforms a natural amino acid into a natural, non-genetically-coded congener. Aba corresponds to a homologation of the alkyl chains normally present in genetically codified amino acids, such as methyl (in Ala) and isopropyl (in Leu), with an ethyl unit. Based on alkyl substitution, this modification can therefore be studied in order to understand its general consequences on the structure-activity relationships in proteins and, in particular, on molecular interactions. This article is part of a Special issue entitled: Posttranslational Protein modifications in biology and Medicine.

Zinc and cadmium complexes of a plant metallothionein under radical stress: desulfurisation reactions associated with the formation of trans-lipids in model membranes. (Chemistry (Weinheim an der Bergstrasse, Germany), 2009)
Metallothioneins (MTs) are sulfur-rich proteins capable of binding metal ions to give metal clusters. The metal-MT aggregates used in this work were Zn- and Cd-QsMT, where QsMT is an MT from the plant Quercus suber. Reactions of reductive reactive species (H(*) atoms and e(aq)(-)), produced by gamma irradiation of water, with Zn- and Cd-QsMT were carried out in both aqueous solutions and vesicle suspensions, and were characterized by different approaches. By using a biomimetic model based on unsaturated lipid vesicle suspensions, the occurrence of tandem protein/lipid damage was shown. The reactions of reductive reactive species with methionine residues and/or sulfur-containing ligands afford diffusible sulfur-centred radicals, which migrate from the aqueous phase to the lipid bilayer and transform the cis double bond of the oleate moiety into the trans isomer. Tailored experiments allowed the reaction mechanism to be elucidated in some detail. The formation of sulfur-centred radicals is accompanied by the modification of the metal-QsMT complexes, which were monitored by various spectroscopic and spectrometric techniques (Raman, CD, and ESI-MS). Attack of the H(*) atom and e(aq)(-) on the metal-QsMT aggregates can induce significant structural changes such as partial deconstruction and/or rearrangement of the metal clusters and breaking of the protein backbone. Substantial differences were observed in the behaviour of the Zn- and Cd-QsMT aggregates towards the reactive species, depending on the different folding of the polypeptide in these two cases.

The Cd(II)-binding abilities of recombinant Quercus suber metallothionein: bridging the gap between phytochelatins and metallothioneins. (Journal of biological inorganic chemistry : JBIC : a publication of the Society of Biological Inorganic Chemistry, 2007)
In this work, we have analyzed both at stoichiometric and at conformational level the Cd(II)-binding features of a type 2 plant metallothionein (MT) (the cork oak, Quercus suber, QsMT). To this end four peptides, the wild-type QsMT and three constructs previously engineered to characterize its Zn(II)- and Cu(I)-binding behaviour, were heterologously produced in Escherichia coli cultures supplemented with Cd(II), and the corresponding complexes were purified up to homogeneity. The Cd(II)-binding ability of these recombinant peptides was determined through the chemical, spectroscopic and spectrometric characterization of the recovered clusters. Recombinant synthesis of the four QsMT peptides in cadmium-rich media rendered complexes with a higher metal content than those obtained from zinc-supplemented cultures and, consequently, the recovered Cd(II) species are nonisostructural to those of Zn(II). Also of interest is the fact that three out of the four peptides yielded recombinant preparations that included S(2-)-containing Cd(II) complexes as major species. Subsequently, the in vitro Zn(II)/Cd(II) replacement reactions were studied, as well as the in vitro acid denaturation and S(2-) renaturation reactions. Finally, the capacity of the four peptides for preventing cadmium deleterious effects in yeast cells was tested through complementation assays. Consideration of all the results enables us to suggest a hairpin folding model for this typical type 2 plant Cd(II)-MT complex, as well as a nonnegligible role of the spacer in the detoxification function of QsMT towards cadmium.

The Cd(II)-binding abilities of recombinant Quercus suber metallothionein: bridging the gap between phytochelatins and metallothioneins. - Domenech, Jordi; Orihuela, Ruben; Mir, Gisela; Molinas, Marisa; Atrian, Silvia; Capdevila, Merce (Journal of biological inorganic chemistry : JBIC : a publication of the Society of Biological Inorganic Chemistry, 2007)
In this work, we have analyzed both at stoichiometric and at conformational level the Cd(II)-binding features of a type 2 plant metallothionein (MT) (the cork oak, Quercus suber, QsMT). To this end four peptides, the wild-type QsMT and three constructs previously engineered to characterize its Zn(II)- and Cu(I)-binding behaviour, were heterologously produced in Escherichia coli cultures supplemented with Cd(II), and the corresponding complexes were purified up to homogeneity. The Cd(II)-binding ability of these recombinant peptides was determined through the chemical, spectroscopic and spectrometric characterization of the recovered clusters. Recombinant synthesis of the four QsMT peptides in cadmium-rich media rendered complexes with a higher metal content than those obtained from zinc-supplemented cultures and, consequently, the recovered Cd(II) species are nonisostructural to those of Zn(II). Also of interest is the fact that three out of the four peptides yielded recombinant preparations that included S(2-)-containing Cd(II) complexes as major species. Subsequently, the in vitro Zn(II)/Cd(II) replacement reactions were studied, as well as the in vitro acid denaturation and S(2-) renaturation reactions. Finally, the capacity of the four peptides for preventing cadmium deleterious effects in yeast cells was tested through complementation assays. Consideration of all the results enables us to suggest a hairpin folding model for this typical type 2 plant Cd(II)-MT complex, as well as a nonnegligible role of the spacer in the detoxification function of QsMT towards cadmium.
The following values have no corresponding Zotero field: accession-num: 17503092
Keywords: cadmium; Cadmium: chemistry; Cadmium–His binding; Drug; Glutathione; Metabolic Detoxication; metallothionein; Metallothionein: chemistry; Metallothionein: metabolism; Phytochelatins; Plant metallothionein; Plant Proteins; Plant Proteins: chemistry; Plant Proteins: metabolism; Protein Binding; Protein Conformation; Quercus; Recombinant Proteins; Sulfide ligands; yeast complementation

Plant metallothionein domains: functional insight into physiological metal binding and protein folding (BIOCHIMIE, 2006)
Plant metallothioneins (MTs) differ from animal MTs by a peculiar sequence organization consisting of two short cysteine-rich terminal domains linked by a long cysteine-devoid spacer. The role of the plant NIT domains in the protein structure and functionality is largely unknown. Here, we investigate the separate domain contribution to the in vivo binding of Zn and Cu and to confer metal tolerance to CUP1-null yeast cells of a plant type 2 NIT (QsMT). For this purpose, we obtained three recombinant peptides that, respectively, correspond to the single N-terminal (N25) and C-terminal (C18) cysteine-rich domains of QsMT, and a chimera in which the spacer is replaced with a four-glycine bridge (N25-C18). The metal-peptide preparations recovered from Zn- or Cu-enriched cultures were characterized by ESI-MS, ICP-OES and CD and UV-vis spectroscopy and data compared to full length QsMT. Results are consistent with QsMT giving rise to homometallic Zn- or Cu-MT complexes according to a hairpin model in which the two Cys-rich domains interact to form a cluster. In this model the spacer region does not contribute to the metal coordination. However, our data from Zn-QsMT (but not from Cu-QsMT) support a fold of the spacer involving some interaction with the metal core. On the other hand, results from functional complementation assays in endogenous MT-defective yeast cells suggest that the spacer region may play a role in Cu-QsMT stability or subcellular localization. As a whole, our results provide the first insight into the structure/function relationship of plant MTs using the analysis of the separate domain abilities to bind physiological metals. (c) 2005 Elsevier SAS. All rights reserved.

Plant metallothionein domains: functional insight into physiological metal binding and protein folding - Domenech, Jordi; Mir, Gisela; Huguet, Gemma; Capdevila, Merce; Molinas, Marisa; Atrian, Silvia (BIOCHIMIE, 2006)
Plant metallothioneins (MTs) differ from animal MTs by a peculiar sequence organization consisting of two short cysteine-rich terminal domains linked by a long cysteine-devoid spacer. The role of the plant NIT domains in the protein structure and functionality is largely unknown. Here, we investigate the separate domain contribution to the in vivo binding of Zn and Cu and to confer metal tolerance to CUP1-null yeast cells of a plant type 2 NIT (QsMT). For this purpose, we obtained three recombinant peptides that, respectively, correspond to the single N-terminal (N25) and C-terminal (C18) cysteine-rich domains of QsMT, and a chimera in which the spacer is replaced with a four-glycine bridge (N25-C18). The metal-peptide preparations recovered from Zn- or Cu-enriched cultures were characterized by ESI-MS, ICP-OES and CD and UV-vis spectroscopy and data compared to full length QsMT. Results are consistent with QsMT giving rise to homometallic Zn- or Cu-MT complexes according to a hairpin model in which the two Cys-rich domains interact to form a cluster. In this model the spacer region does not contribute to the metal coordination. However, our data from Zn-QsMT (but not from Cu-QsMT) support a fold of the spacer involving some interaction with the metal core. On the other hand, results from functional complementation assays in endogenous MT-defective yeast cells suggest that the spacer region may play a role in Cu-QsMT stability or subcellular localization. As a whole, our results provide the first insight into the structure/function relationship of plant MTs using the analysis of the separate domain abilities to bind physiological metals. (c) 2005 Elsevier SAS. All rights reserved.
The following values have no corresponding Zotero field: pub-location: 23 RUE LINOIS, 75724 PARIS, FRANCE publisher: ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER
Keywords: Cu-aggregates; metallothionein; MT dimers; Quercus suber; separate Cys-rich domains; spacer region; yeast complementation; Zn-aggregates